Changes in the Composition of Biologically Active Compounds during the Ripening Period in Fruit of Different Large Cranberry (Vaccinium macrocarpon Aiton) Cultivars Grown in the Lithuanian Collection - Rima Šedbarė; Izolda Pašakinskienė; Valdimaras Janulis (Plants, 2023)
In our investigation, we evaluated the content of chlorogenic acid, proanthocyanidins, anthocyanins, flavonols, triterpenoids, and phytosterols in cranberry fruit extracts of the cultivars ‘Baifay’, ‘Early Black’, ‘Howes’, ‘Pilgrim’, ‘Red Star’, and ‘Stevens’ grown in Lithuania, as well as changes in the antioxidant activity in extracts of fruit samples of these cultivars during the period of berry maturation. The highest amount of proanthocyanidins (8.87 ± 0.57 mg EE/g EE) and flavonols (3688.52 ± 22.85 µg/g) was determined in cranberries of the cultivar ‘Howes’ harvested on 12 August. Remarkably, the highest anthocyanins content (9628.62 ± 266 µg/g) was determined in cranberries of the cultivar ‘Howes’ harvested on 22 October. The study showed that the content of phytochemical compounds in cranberries varied between 12 August and 22 October; the content of proanthocyanidins decreased by a factor of about 2, the content of chlorogenic acid decreased by a factor of about 1.3, the content of flavonols decreased by a factor of about 2, and the content of anthocyanins increased by 27 to 450 times. A strong correlation was found between the total proanthocyanidin content of cranberry fruit extracts and their in vitro antiradical and reducing activity (r = 0.781 and 0.726, respectively, p < 0.001). The data of our study detail the accumulation of the phytochemical composition of biologically active compounds in cranberry samples during the stages of maturity, therefore these data are significant for the assessment of harvest time of cranberry and can be applied to select cranberry cultivars for further cultivation in Lithuanian climatic conditions.